The views of media elites on the reality of citizen journalism and its commitment to professional and ethical standards - Hassan, Ahmed Falah; Hassan, Saad Kadhim (ALBAHITH ALALAMI, 2022)
This article aims to identify the views of media elites on citizen journalism, a new media genre that strays away from the foundations and ethics of professional journalism, thus calling for in-depth exploration and scrutiny into the genre and its commitment to the professional standards of journalism.For this purpose, the researcher opted for the survey method by distributing a questionnaire to a purposive sample consisting of 407 media elites. The research is also based on Habermas' public sphere theory.